Dissecting the contribution of human chromosome 21 syntenic regions to recognition memory processes in adult and aged mouse models of Down syndrome - Canonica, Tara; Kidd, Emma J.; Gibbins, Dorota; Lana-Elola, Eva; Fisher, Elizabeth M. C.; Tybulewicz, Victor L. J.; Good, Mark (Frontiers in Behavioral Neuroscience, 2024)
Trisomy of human chromosome 21 (Hsa21) results in a constellation of features known as Down syndrome (DS), the most common genetic form of intellectual disability. Hsa21 is orthologous to three regions in the mouse genome on mouse chromosome 16 (Mmu16), Mmu17 and Mmu10. We investigated genotype-phenotype relationships by assessing the contribution of these three regions to memory function and age-dependent cognitive decline, using three mouse models of DS, Dp1Tyb, Dp(17)3Yey, Dp(10)2Yey, that carry an extra copy of the Hsa21-orthologues on Mmu16, Mmu17 and Mmu10, respectively. At adult age (12-13 months old), the three mouse models showed normal novel object recognition memory. However, adult Dp1Tyb, but not Dp(17)3Yey or Dp(10)2Yey mice, showed impaired associative spatial recognition memory. At 18-20 months of age, Dp(10)2Yey but not Dp1Tyb or Dp(17)3Yey mice, displayed a selective deficit in novel object recognition memory. Hippocampal glutamate receptor expression was altered in adult Dp1Tyb and aged Dp(10)2Yey mice, but unaltered in Dp(17)3Yey mice. Our results show that distinct Hsa21orthologous regions contribute differentially to cognitive dysfunction in DS mouse models and that aging may interact with triplication of Hsa21-orthologous genes on Mmu10.